2021
DOI: 10.1038/s41598-021-90442-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with discontinuation of ts/bDMARDs in rheumatic patients from the BIOBADASER III registry

Abstract: Biologic and targeted synthetic disease-modifying antirheumatic drugs (ts/bDMARDs) play a pivotal role in the treatment of rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS). Persistence of therapy provides an index of a drug’s overall effectiveness. The objective of the study was to identify factors associated with discontinuation of ts/bDMARDs in a real-world dataset. The study population comprised patients diagnosed with RA, PsA, and AS included in the BIOBADASER registry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
2
9
2
Order By: Relevance
“…Different studies have reported 3-, 4-, or 5-year retention rates for golimumab ranging from 35% to 65% (Aaltonen et al, 2017;Alegre-Sancho et al, 2021;Chimenti et al, 2022;Michelsen et al, 2020;Serrano_Benavente et al, 2022;Thomas et al, 2018), and a systematic review reported 3-year golimumab retention rates of 32%-67% (Svedbom, Storck et al, 2017). To the best of our knowledge, the Navarini et al, 2020;Prior-Español et al, 2021) appears to be greatest when they are used as first-line biological DMARD therapy, an observation which is consistent with our findings in the current analysis. The probability of retention at year 1 was 81.7% when golimumab was administered as first-line therapy compared with 69.9% when it was given as second-line therapy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Different studies have reported 3-, 4-, or 5-year retention rates for golimumab ranging from 35% to 65% (Aaltonen et al, 2017;Alegre-Sancho et al, 2021;Chimenti et al, 2022;Michelsen et al, 2020;Serrano_Benavente et al, 2022;Thomas et al, 2018), and a systematic review reported 3-year golimumab retention rates of 32%-67% (Svedbom, Storck et al, 2017). To the best of our knowledge, the Navarini et al, 2020;Prior-Español et al, 2021) appears to be greatest when they are used as first-line biological DMARD therapy, an observation which is consistent with our findings in the current analysis. The probability of retention at year 1 was 81.7% when golimumab was administered as first-line therapy compared with 69.9% when it was given as second-line therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Retention of golimumab (Hernandez et al., 2019; Pombo‐Suarez et al., 2021) and other biological DMARDs (González‐Fernández et al., 2019; Navarini et al., 2020; Prior‐Español et al., 2021) appears to be greatest when they are used as first‐line biological DMARD therapy, an observation which is consistent with our findings in the current analysis. The probability of retention at year 1 was 81.7% when golimumab was administered as first‐line therapy compared with 69.9% when it was given as second‐line therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, we found no significant correlation between the number of CVD risk factors and treatment discontinuation specifically attributed to adverse events. This outcome contradicts the findings from the BIOBADSER registry, which found an association between higher comorbidity index (including CVD) and discontinuation of b/tsDMARDs due to adverse events 15 . These differences may be attributed to variations in cohort characteristics or strategies employed to mitigate the risk of adverse events across different countries or regions.…”
Section: Discussioncontrasting
confidence: 77%
“…In fact, patients stratified for the presence of comorbid disease had a significantly lower retention rate (60% vs. 90%, p < 0.0007), up to 3 years. The presence of comorbidities would be expected to negatively impact upon drug adherence since these patients tend to have a higher rate of treatment interruption due to complications [31][32][33].…”
Section: Discussionmentioning
confidence: 99%